Health Services Utilization Among Children With and Without Autism Spectrum Disorders - Cummings, Janet R.; Lynch, Frances L.; Rust, Kristal C.; Coleman, Karen J.; Madden, Jeanne M.; Owen-Smith, Ashli A.; Yau, Vincent M.; Qian, Yinge; Pearson, Kathryn A.; Crawford, Phillip M.; Massolo, Maria L.; Quinn, Virginia P.; et al. (Journal of autism and developmental disorders, 2016)
Using data from multiple health systems (2009–2010) and the largest sample to date, this study compares health services use among youth with and without an autism spectrum disorder (ASD)—including preventive services not previously studied. To examine these differences, we estimated logistic and count data models, controlling for demographic characteristics, comorbid physical health, and mental health conditions. Results indicated that youth with an ASD had greater health care use in many categories, but were less likely to receive important preventive services including flu shots and other vaccinations. An improved understanding of the overall patterns of health care use among this population could enable health systems to facilitate the receipt of appropriate and effective health care.